Vegetation Analysis as Indicator of Mangrove Degradation Level in Keboromo Village, Tayu - M. Amanun Tharieq; Azis Nur Bambang; Lita Tyesta Addy Listya Wardhani; Sri Redjeki; Rudhi Pribadi (Jurnal Kelautan Tropis, 2023)
Mangrove degradation is one of the most common issues in the coastal areas of Java, which can cause ecological impacts and even disadvantage for local community. The mangrove forest degradation can be identified based on the vegetation analysis results, which could potentially contribute to the mangrove ecosystem management and rehabilitation programs in the coastal areas. Mangroves in Keboromo Village was the rehabilitation and cultivation area, but often get damaged by ocean waves. This study aims to determine the ecological and vegetation conditions of mangrove ecosystems consist of species composition, density, canopy cover, tree height, and environmental parameters were held in February 2023. The method used was direct observation using transect quadrants of 10x10 m2. The average mangrove density of all observation stations was 3.425 individuals/ha for the tree category, 575 individuals/ha for the sapling category, and 250 individuals/ha for the seedling category. The average percentage of canopy cover was 78.41%. The average height of mangrove trees at all stations is 4.15 m. The environmental parameters were still compatible with the water quality standard for biota and mangrove life. The mangrove forest degradation level based on standard criteria and guidelines for determining mangrove degradation is categorized as low, indicated by mangrove density >1500 individuals/ha and canopy cover >75%. Poor conditions were measured for sapling and seedling densities, which may be caused by environmental factors unsupportive for mangrove regeneration. Based on the results of mangrove vegetation analysis in Keboromo Village, it can state the mangrove ecosystem condition is good. However, management programs are needed to keep the mangroves sustainable.